415 Line1 Derepression in Specific Retrotransposon Families in Aged Mice Leads to Cytosolic DNA and Increased Inflammation. (April 2022) - Martinez, John; Simon, Matthew; Seluanov, Andrei; Gorbunova, Vera
Abstract : OBJECTIVES/GOALS: The major objective of this project is two points. First, is to repeat and confirm previous observations that there is elevated cytosolic Line1 DNA in the cytoplasm of cells derived from old mice compared to young. Second is to identify which Line1s in the genome are contributing to this free DNA and test if targeting them rescues the age-related phenotype. METHODS/STUDY POPULATION: This project will focus on data collected from both tissues and primary cells derived from multiple tissues. Using cellular/tissue fractionation kits, we isolate specifically from the cytoplasm. This specificity is confirmed by western blotting. Measurement of the Line1 levels is measured by quantitative PCR. Subsequently, these cytoplasmic samples are sent off for sequencing in order to quantify the length of the free DNA in the cytoplasm and to identify which Line1 genomic families the cytosolic DNA originates. Additionally, FISH is utilized to visualize Line1 DNA in the cytoplasm of aged versus young cells RESULTS/ANTICIPATED RESULTS: We anticipate this research to confirm the hypothesis that extranuclear Line1 DNA accumulates with age in both tissues and primary fibroblasts. Additionally, we expect to be able to determine which specific families of genomic Line1 is driving this extranuclear DNA, which would suggest the active retrotransopable elements that are directly involved in this aging related phenotype. Assuming successful identification of such families, we can then target and silence these specific elements to determine not only if cytoplasmic Line1 in aged mice decreases, but additionally if the healthspan and/or lifespan of these mice improves DISCUSSION/SIGNIFICANCE: Dereoressed Line1s have been shown to be involved in detrimental phenotypes, including autoimmune disease, cancer, and inflammaging. Targeting retrotransposons, either directly through degradation of transcriptional product of LINE1s or indirectly by improving function of regulators, will be crucial in ablating aging phenotypes